2023
DOI: 10.1177/17562864231200627
|View full text |Cite
|
Sign up to set email alerts
|

Disease activity 4.5 years after starting cladribine: experience in 264 patients with multiple sclerosis

Kimberley Allen-Philbey,
Stefania De Trane,
Amy MacDougall
et al.

Abstract: Background: Cladribine is an effective immunotherapy for people with multiple sclerosis (pwMS). Whilst most pwMS do not require re-treatment following standard dosing (two treatment courses), disease activity re-emerges in others. The characteristics of pwMS developing re-emerging disease activity remain incompletely understood. Objectives: To explore whether clinical and/or paraclinical baseline characteristics, including the degree of lymphocyte reduction, drug dose and lesions on magnetic resonance imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Long-term suppression of MS disease activity beyond the 4-year period studied in the CLARITY trial and its extension is therefore clearly possible. One real-world study showed that 26% of people with MS treated with CladT demonstrated recurrent MS disease activity during a median follow-up period of 4.5 years and that this was associated with higher MRI activity at baseline and receipt of a lower than indicated dose for the second course of CladT [ 79 ]. Another registry-based study found that 74% of a Clad-T-treated population achieved NEDA-2 during year 4 of treatment of a population with highly active MS [ 80 ].…”
Section: Patient Management After Initiation Of Cladribine Tabletsmentioning
confidence: 99%
“…Long-term suppression of MS disease activity beyond the 4-year period studied in the CLARITY trial and its extension is therefore clearly possible. One real-world study showed that 26% of people with MS treated with CladT demonstrated recurrent MS disease activity during a median follow-up period of 4.5 years and that this was associated with higher MRI activity at baseline and receipt of a lower than indicated dose for the second course of CladT [ 79 ]. Another registry-based study found that 74% of a Clad-T-treated population achieved NEDA-2 during year 4 of treatment of a population with highly active MS [ 80 ].…”
Section: Patient Management After Initiation Of Cladribine Tabletsmentioning
confidence: 99%